Ticks (Acari : Ixodidae) parasitizing humans in an Atlantic rainforest reserve of Southeastern Brazil with notes on host suitability - Szabo, Matias P. J.; Labruna, Marcelo B.; Castagnolli, Karina C.; Garcia, Marcos V.; Pinter, Adriano; Veronez, Viviane A.; Magalhaes, Georgia M.; Castro, Marcio B.; Vogliotti, Alexandre (Springer, 2006)
While conducting projects on ticks from deer and on tick ecology in animal trails in an Atlantic rainforest reserve in Southeastern Brazil, researchers of our group were bitten by ticks several times. Some of these episodes were recorded. Three species of adult ticks attached to humans: Amblyomma brasiliense Aragauo, Amblyomma incisum Neumann, and Amblyomma ovale Koch. Eight nymphal attachments with engorgement on humans were recorded. From these, six molted to adults of A. incisum, one to an adult of A. brasiliense, and one had an anomalous molting, therefore the adult tick could not be properly identified. Local reactions to tick attachment varied among individual hosts from almost imperceptible to intense. Especially itching, but hyperemia and swelling as well, were prominent features of the reaction. Overall it can be affirmed that human beings can be a physiologically suitable host species for ticks in the Atlantic rainforest and that itching was an important if not the major component of the resistance to tick bite.
Keywords: Ixodidae; human bite; Amblyomma incisum; Amblyomma brasiliense; Amblyomma ovale; Atlantic rainforest; itching; Brazil